Problems of Learning the First Muallimin Qiro'ah at the Baitul Mustaqim Punggur Islamic Boarding School Central Lampung | Permasalahan Pembelajaran Qiro’ah Muallimin Pertama di Pondok Pesantren Baitul Mustaqim Punggur Lampung Tengah - Vina Apriliana; Mar'atus Sholihah; Eva Lathifah Fauzia (NAJAH BESTARI, 2023)
This study aims to determine the difficulties faced by students at the Baitul Mustaqim Islamic Boarding School in qiro'ah Arabic writing. This research uses qualitative methods and this research uses interview results as a technique for data collection. The main informer in this study was the Arabic teacher, and the additional informer was the head of the Diniyah madrasah of the Baitul Mustaqim Islamic Boarding School. Based on the results of research, it is known that the difficulty of learning material or subjects that use the qiro'ah method is starting from makharijal-surat, shifat surat, tajweed law, and grammar, while in makharij al-surat, shifat al-surat and tajweed there are some students who are weak in qira'ah Arabic writing but also many of the students who already have good abilities. The results suggest that the learning of makharij al-surat, shifat al-surat and tajweed is carried out intensively By adding a takhasus schedule for students who are weak in ability. Therefore, grammatical reinforcement in the form of ascetics becomes increasingly important. For this reason, synchronizing material in Islamic boarding schools with the Ministry of Religion can be an alternative.